Implementation of Alumni Cooperation Program Development with Polytechnic College of Administrative Sciences, State Administrative Institution Jakarta - Kamil, Faishal Ahmad; Solihati, Keisha Dinyah; Handayani, Nida (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2024)
This research investigates the development and implementation of the alumni collaboration program at Politeknik Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara (STIA LAN) Jakarta. The background highlights the need for fostering stronger alumni connections with the institution to enhance educational quality, support, and career opportunities for graduates. The main objectives of the research are to evaluate the effectiveness of alumni engagement, examine challenges, and propose solutions for improving the collaboration program. The research utilizes a qualitative approach, focusing on literature reviews and data analysis to identify key aspects of alumni involvement, including communication platforms, alumni contributions to curriculum development, and career support programs. The results show that while the alumni collaboration program has the potential to strengthen institutional ties, several challenges persist, such as low alumni participation, limited awareness of the program’s benefits, and an ineffective organizational structure. The study suggests that improvements in digital platforms, structured mentoring programs, and enhanced alumni recognition can foster stronger engagement and participation. Additionally, it emphasizes the importance of continuous evaluation to refine the program. The conclusion suggests that a well-implemented alumni collaboration program not only benefits alumni but also enhances the institution’s reputation, supports curriculum development, and strengthens ties with the broader professional community. Thus, fostering sustainable alumni engagement is crucial for STIA LAN Jakarta’s long-term growth and the success of its graduates in the workforce.